APRESIASI MASYARAKAT TERHADAP KEBIJAKAN PEMBLOKIRAN PORNOGRAFI DI INTERNET - Hamjen, Hilarion (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2012)
The research was conducted in the capital of South Borneo and Central Borneo to describe about peoples appreciation to the policy of cyberporn blocking. The research was conducted with quantitative survey method. The results illustrate that the most of people have positive appreciation to the the policy, because they think the policy is able to reduce the negative effects of pornography, however most of them do not know about the policy. They think the widespread of cyberporn because the lack of monitoring and enforcement to cyberporn. So the Ministry of communication and information need more intensive socialization and control the cyberporn.